(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The study aimed to identify the impact of social media applications on psychological disorders among students of faculties of arts and education in Saudi and Jordanian universities. The research based on the descriptive approach. The study sample consisted of (2776) students from the Faculty of Arts and Education in the second, third and fourth years in Saudi Arabia and Jordan. The study used a questionnaire to collect the research data while the statistical package for social sciences (SPSS) was applied in order to analyze the data and come up with the result. The results showed that students in the arts and education colleges in Saudi Arabia use social media applications around 76% while using percentage among Jordanian students reached 71%. The results of the differences also showed that there are significant differences between students of the faculties of arts and education in Saudi Arabia and Jordan in the incidence of some mental disorders. The results also showed a statistically significant relationship between the use of social media applications and disorders among students of faculties of arts and education in Saudi Arabia and Jordan according to gender. The study has recommended that it is necessary to activate the unit of psychological counseling and academic universities to guide students and guide them to use social media applications in the right way. In addition to that, the researchers recommends that universities should directing students and addressing Psychological and academic issues for university students, and provide continuous assistance to them by reducing the level of feelings of psychological and social disorders and communication skills.